Acute under back pain. A clinical therapeutic approach. - Gamez Morales, Lorenzo (Revista Universidad de Guayaquil, 2013)
In this work, present a review about the clinical evaluation, electrofisiologies and imagines studies in acute lumbalgy, with personal reflections about this theme. Is high the incidence of patients with this clinical problem. Is very important the clinical evaluation for the correct determination of the areas of pain and the use of the diagnosis methods to etiology definition. Is very important in the therapeutics of the under back pain the use of all the methods to reduces the pain.